Memory of the Holocaust Iremos con vosotros hasta el fin, of María Teresa León: a heroic song to Poland - Núñez Molina, María Lourdes (Hispania Nova, 2019)
Along with by her family, María Teresa León walks through the Auschwitz death camp. The reflection of this anguished experience was evoked in her memories and surely induced her to write Iremos con vosotros hasta el fin. In this work, conceived as a radio theatrical script, María Teresa praises the solidarity and sacrifice of a Polish couple, who shelter of a group of Polish Jewish children. When the children were selected to enter the gas chambers of Auschwitz in the spring of 1943, they decided not to abandon them and die next to them. Iremos con vosotros hasta el fin is a tribute to the victims, an exhortation to present and future generations to remember the horror of the Holocaust, because forgetfulness leads to the resurgence of evil.
Keywords: Holocaust; Jews; María Teresa León; Poland; Auschwitz; fiction